A facile methodology to make the glass surface superhydrophobic - Nidchamon Jumrus (2020)
© 2020 Elsevier B.V. In this work, the glass surface was successfully modified via low-temperature annealing and wet etching techniques. Hydrophilic/superhydrophobic of the modified glass surface was then transformed after dipped with methyltrichlorosilane (MTCS). Morphology and structural properties of the samples were analyzed by scanning electron microscopy, atomic force microscopy, fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. The results exhibit that micro/nano roughness was observed on the annealed/etched glass surface. Interestingly, the wettability of the annealed and etched glass abruptly transformed to superhydrophobic with a water contact angle of 154° and a sliding angle of 3° after coating with MTCS. Annealing assisted etching technique not only plays an important role in changing of roughness in nanoscale by reducing residual and hardness but also changes the formation of polysiloxane from microspheres to nanofilaments on the surface.